Characterization of PD-1/PD-L1 immune checkpoint expression in the pathogenesis of musculoskeletal Langerhans cell histiocytosis: A retrospective study. Issue 43 (29th October 2021) - Hashimoto, Kazuhiko; Nishimura, Shunji; Sakata, Naoki; Inoue, Masami; Sawada, Akihisa; Akagi, Masao
Abstract : Abstract: Recent data suggest that programmed cell death -1 (PD-1) and programmed cell death ligand-1 (PD-L1) are involved in the pathogenesis of Langerhans cell histiocytoma (LCH); however, their contributions are not well established. Also, the involvement of PD-1/PD-L1 molecules in musculoskeletal LCH remains particularly unclear. The current study aims to characterize the involvement of PD-1/PD-L1 immune checkpoint system in the pathogenesis of musculoskeletal LCH. PD-1/PD-L1 expression was evaluated in 6 patients, 3 men and 3 women with a mean age of 13.5 years, with musculoskeletal LCH who were treated at Kindai University Hospital and Osaka Women's and Children's Hospital between November 2005 and December 2020. The median follow-up period for all patients with musculoskeletal LCH was 41 months. We surveyed symptoms, number of lesions, treatment modality, and outcomes. Immunostaining for CD4, CD8, PD-1, and PD-L1 was also performed on pathological specimens obtained by biopsy. Multiple lesions were observed in 5 cases, and a single lesion was observed in 1 case. The chief complaint in 5 cases was pain. Four patients underwent spontaneous regression. The other 2 patients received chemotherapy. The outcomes included continuous disease-free (n = 5) and alive with the disease (n = 1). The CD4-, CD8-, PD-1-, and PD-L1-positive rates among all specimens were 100%, 100%, 16.6%, and 83.3%, respectively. The CD4/PD-L1, CD8/PD-L1, and PD-1/PD-L1 positive rates in all the specimens were 83.3%, 83.3%, and 16.6%, respectively. We believe that the PD-1/PD-L1 immune checkpoint molecules may play some role in the microenvironment of musculoskeletal LCH.